An Investigation on Mechanical and Physical Properties of Recycled Coarse Aggregate (RCA) Concrete with GGBFS - Tufekci, Muzaffer Mansur; Cakir, Ozgur (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
An experimental program was carried out to investigate the usability of recycled coarse aggregate (RCA) concrete with and without ground granulated blast furnace slag (GGBFS). The RCA was derived from concrete having compressive strength of 47.6 MPa. Twelve concrete mixtures having various RCA (0-25-50-100%) and GGBFS (0-30-60%) replacement levels were designed with a water-to-binder (w/b) ratio of 0.50. Fresh concrete properties were observed through workability and slump loss. Compressive strength, tensile splitting strength, bond strength, ultrasonic pulse velocity, water absorption and density of hardened concretes were also determined at 7 and 28 days and the relations between physical properties and mechanical properties of RCA concretes with/without GGBFS were investigated. The RCA content significantly improved the tensile splitting strength of the concrete according to the compressive strength and the use of 60% GGBFS content in RCA concrete had a marginal increasing effect on the tensile splitting strength. The mixes containing 100% RCA was found to be noticeably beneficial in terms of the bond strength and the highest bond strengths were obtained with the use of 60% GGBFS content in RAC for all series at 28 days. However the lowest density and the greatest water absorption was obtained for RAC and an inverse relationship between the density and the water absorption ratio was determined.
Keywords: Recycled coarse aggregate; GGBFS; Mechanical properties; Physical properties; Regression analysis; COMPRESSIVE STRENGTH; FLY-ASH; PERFORMANCE; DURABILITY; BEHAVIOR; WASTE; Engineering